Evaluación del control interno del cuerpo de bomberos de Ventanas en el periodo 2020-2021. - Mérelo Bermeo, Helen Lisbeth (2022)
This case study to be conducted in the company of the fire departament of the canton of ventanas consists of the theme, “Evaluation of the internal control of the ventanas fire Department in the period 2020-2021”, internal control is essential within the Company especially because it manages to monitor, control and especially prevent risks or fraud and especially take care of all assets, resources and interests of the Company to evaluate how it is conducting the activities of the same and see its efficiency of operations. At the time of applying the evaluation of internal control in the fire department of the city of Ventanas, it will be recognized how the control and the procedures of the five components are applied in the audit, which will allow the efficiency of is control systems to be carried out by the administrative management with the purpose of generating a reasonable security in the operational and financial procedures of the Company to meet the goals objectives of the financial and operational planning of the Company that have been established. In the Company we verified all the procedures that should be carried out for internal control evaluations to verifity the records, search for information, recognize if the information is accurate, recommendations for the evaluation of internal control, the way the fire department of the cantón of Ventana is managed and especially to know a Little of its history.